A Review On Novel Drug Delivery System - Niosomes - Maurya, Ruchi; Pathak, Kadambari; Saxena, Priya; Tiwari, Juhi (Asian Journal of Pharmaceutical Research and Development, 2013)
Drug delivery aims at delivering the drug at a particular site. Novel drug delivery is a recent system that promotes easy and convenient route of administration and are also advantageous over conventional dosage form. Niosomes are novel drug delivery that promotes formations of vesicles by hydrating the mixture of cholesterol and non-ionic surfactants. Targeted drug delivery can also be achieved using niosomes where the drug is directly delivered to the body part where the therapeutic effect is required. Thereby reducing the dose required to be administered to achieve the desired effect. The therapeutic efficacy of the drugs is improved by reducing the clearance rate, targeting to the specific site and by protecting the encapsulated drug. Drug targeting reduces the dose which leads to subsequent decrease in the side effects.